KEUNGGULAN PRODUK BERBASIS KOMPETENSI PENGETAHUAN PASAR DALAM MENINGKATKAN KINERJA PEMASARAN - Ageng Prasetyo; Mochamad Purnomo (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2020)
This study focus on how the company need to know about the market expectation before the product was launched esspecially in Kelompok Pengrajin Krupuk Rambak Desa Penanggulan, Pegandon, Kendal in 2019.The ability of the company to know the market was called the market knowledge competence. Its concist of three major aspects such as customer knowledge competence, competitor knowledge competence and the interface between R&D with marketing department. The higher market knowledge competence was predicted can creates the higher the competitive advantage in the market place. And as the result the competitive advantagecan increase the marketing performance, these was inluded sales volume, sales growth and customers growth.Populations of this study were 1000 customers of Kelompok Pengrajin Krupuk Rambak Desa Penanggulan, Pegandon, Kendal, and the samples of this study were 100 customers which devided into 2 categories of monthly purchases amount. We expected this study could be applied in the company in order to support policies and strategies in the marketing field mainly on developing new products.